A New System Based on Web Services and Rfid for Tracking People in a Pervasive Mining Environment - Soto-Gomez, J (IEEE Computer Society, 2013)
This work present a solution for locating people inside of mines with a system designed with the service oriented architecture and RFID technology to help the security of workers. We propose a pervasive computing system designed with a UML process extension, to discover the rights web services to transmit and process data collected from RFID sensors. The data captured from nodes allow calculating the location of workers and machines by reference tags in conjunction with techniques of trilateration. The results were successful, since it achieves a design of pervasive system with web services and a database model to be used by localization algorithm that shown an improvement in its accuracy with an increasing the number of reference tags. © 2013 IEEE.